Social moods in Romania at the brink of the revolution of 1989 in the light of the reports from the Polish embassy in Bucharest - Kastory, Agnieszka (Balcanica Posnaniensia. Acta et studia, 2020)
The aim of the article is to show the perception of the situation in Romania before the so-called Romanian revolution of 1989 on the basis of the notes and reports from the Polish embassy in Bucharest. Different texts of Romanian dissidents, critical towards the communist regime of Nicolae Ceauşescu, were included in these sources. The Polish officials noticed each manifestation of resistance against the regime and followed the process of concretization of an organized opposition. From their point of view, isolated protests, expressed in the form of open letters to President Ceauşescu or the chairman of the Writers' Union, did not foreshadow any imminent fall of the Romanian dictator. However, they became the evidence of the Romanians' complete rejection of the existing political system. The content and form of all interpreted protests show understanding and correct recognition of the sources of the catastrophic situation of Romania. The events of December 1989 confirmed that Romanians were ready to completely reject the existing social, economic and political system.